The restoration of the Church of England Canterbury diocese and the archbishop's peculiars - Reid, Tom (Church of England Record Society (Series), 2022)
A complete transcription of the Lambeth Library MS 1126. Lambeth Library MS 1126 was compiled, probably in late 1663, on behalf of Gilbert Sheldon, the new archbishop of Canterbury, as a conspectus of the parishes of Canterbury diocese and the archiepiscopal peculiars. A number of entries contain illuminating comments on the religious complexion of the parish, relating to both its incumbents and leading laity, of a type not found elsewhere for the 1660s. Its value for historians is twofold: first, the light it throws on the restoration of the episcopalian Church of England in the early 1660s. Notwithstanding the Act of Uniformity enforced at St Bartholomew's Day 1662, it is abundantly clear from this Catalogue that the Church of England remained divided and unsettled in the parishes, at least in Canterbury diocese. Second, the Catalogue is of interest for the administrative processes it records, as an incoming archbishop, necessarily non-resident, sought to become acquainted with the clergy and prominent laity in the parishes, information which was then updated over the next twenty years. In this respect, the Catalogue adumbrates the more routine and fuller collection of information about the parishes in the eighteenth-century church. A few of the comments in the Catalogue have already been referred to by historians, but this complete transcription has allowed in-depth analysis and concludes that Canterbury diocese must have experienced many more ejections of clergy than has previously been recognized, pointing to a need for more detailed examination of events in other dioceses